2018
DOI: 10.1021/acsami.8b01631
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Directed Parallel Alignment Architecting 3D Lithium-Ion Pathways within Solid Composite Electrolyte

Abstract: It is of great significance to seek high-performance solid electrolytes via a facile chemistry and simple process for meeting the requirements of solid batteries. Previous reports revealed that ion conducting pathways within ceramic-polymer composite electrolytes mainly occur at ceramic particles and the ceramic-polymer interface. Herein, one facile strategy toward ceramic particles' alignment and assembly induced by an external alternating-current (AC) electric field is presented. It was manifested by an in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 37 publications
0
46
0
2
Order By: Relevance
“…Later,t he same group reported that HSSE with aligned LLTO nanowires exhibits one order of magnitude higheri onic conductivity than that with randomly aligned nanowires as displayed in Figure 4a and b. [38] Such 3D HSSE possesses an ionic conductivity of 2.4 10 À6 Scm À1 at room temperature without lithium salts, which is notably higher than random structure( 8.0 10 À7 Scm À1 ). Yang and co-workers designedv ertically aligned and inter-con-nectedL ATPn anowires via an ice-templating-based method, which have been encapsulated into PEO matrix to fabricate PEO-LATP HSSE.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 92%
See 1 more Smart Citation
“…Later,t he same group reported that HSSE with aligned LLTO nanowires exhibits one order of magnitude higheri onic conductivity than that with randomly aligned nanowires as displayed in Figure 4a and b. [38] Such 3D HSSE possesses an ionic conductivity of 2.4 10 À6 Scm À1 at room temperature without lithium salts, which is notably higher than random structure( 8.0 10 À7 Scm À1 ). Yang and co-workers designedv ertically aligned and inter-con-nectedL ATPn anowires via an ice-templating-based method, which have been encapsulated into PEO matrix to fabricate PEO-LATP HSSE.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 92%
“…Recently,3 Dc onnected necklace-likeL ATPw ith poly(ethylene glycol) diacrylate (PEGDA) and poly(dimethylsilone) (PDMS)h as been constructed by applying externalalternating-current electric field. [38] Such 3D HSSE possesses an ionic conductivity of 2.4 10 À6 Scm À1 at room temperature without lithium salts, which is notably higher than random structure( 8.0 10 À7 Scm À1 ). As shown in Figure 4d,anovel hydrogel derived pre-percolated 3D LLTO framework was designed and fully embeddedi nP EO matrix as HSSE.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 93%
“…[103] The ionic conductivity (0.52 10 À4 Scm À1 )o ft he vertically aligned structure is 3.6 times that of the composite electrolyte with randomly dispersed LATP NPs. [104] They found that the roomtemperature ionic conductivity of these 3D channels was three times highert han that of the randomo ne. [104] They found that the roomtemperature ionic conductivity of these 3D channels was three times highert han that of the randomo ne.…”
Section: Composite Solid Electrolytementioning
confidence: 99%
“…Liu et al employed LATP@PEGDA@PDMS (x = 0.3 in LATP) assembled into 3D connected networks by applying an externala lternating current (AC) electric field. [104] They found that the roomtemperature ionic conductivity of these 3D channels was three times highert han that of the randomo ne. Lei et al synthesized LATP (x = 0.3) from as olutionm ethod and then prepared composite electrolyte materials (CEM) with LATP and poly(vinylidene fluoride) (PVDF) in differentr atios.…”
Section: Composite Solid Electrolytementioning
confidence: 99%
“…Moreover, design of new nanofillers that show unique interactions with ions is another viable approach to realizing fast ion conduction. To that end, numerous ion‐conductive inorganic nanofillers, such as Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 , Li 0.3 La 0.557 TiO 3 , and Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , have been investigated, which showed the capability of more effectively building fast pathways for ion‐conduction owing to their intrinsic ability of migrating Li + . Further, in addition to particle‐based nanofillers, there were emerged considerable studies on 1D ion‐conductive nanofillers that helped build more continuous and efficient pathways for rapidly transporting Li + depending on the polymer–filler interfaces or the nanofillers themselves.…”
Section: Introductionmentioning
confidence: 99%